External Request Modifications in Yemeni Arabic as Used by Male-Male and Male-Female Interactions - Yahya Mohammed Al-Marrani (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2018)
The current study explores the types and frequency of external request modifications in Yemeni Arabic as produced by male speakers the study participants were 336 undergraduate students (168 male participants and 168 female participants) from Sana’a University, aged 20-23. All of the participants are relatively homogeneous in terms of their cultural background. The data were collected by using Discourse Completion Test (DCT).The analysis of the data is based on Blum-Kulka et al’s (1989) CCSARP (Cross Cultural Speech Act Realization Project) coding scheme. The results of the study showed that the male speakers generally showed greater use of external request modification to mitigate their requests. Seven external request modifications were identified in the data of the present study in M-M, M-F interactions. However, in M-M interactions, the number of external request modifications, which were identified in the data, was 2006. On the other hand, in M-F interactions the number of external request modification was 2016. The results revealed that Yemeni males showed greater use of the external request modification when interacting with females more than to males.